Teaching Qualities and Perception towards Mathematics Professor by LICT Students’: Self-Appraisal Survey - Khanal, Ramesh (Journal of Balkumari College, 2024)
This study studied the perception of Lumbini Information and Communication Technology (LICT) Campus students’ towards mathematics professors (MP) also examining the teaching qualities. The aim of this study was to identify the level of perception, teaching quality, and behavior of MP and tried to find out that how the MP’s communication skills, topics presentation, and guidance towards students was. The population of the study compared all students of LICT Campus. The study sample consisted 376 students selected through the cluster and simple random sampling techniques from the Campus domain mail. The cross-sectional survey design was used and 26.06 % of data was collected from 24 self-made Five Likert scale (very poor to excellent) by questionnaires through a google form. Data were analyzed by descriptive statistics using SPSS 20. The total number of male respondents were 72.20%, 70.20% were first-year and 57.6% were CSIT students. The descriptive statistic showed the class management was more consistent than other teaching qualities and that MP was friendly, never rude and biased but proud. We concluded that professors should be well communicating, presenting the subject matter confidently, motivating towards research activities, and behave friendly and peaceful.